2016
DOI: 10.1177/1591019916632369
|View full text |Cite
|
Sign up to set email alerts
|

ARTS (Aspiration–Retriever Technique for Stroke): Initial clinical experience

Abstract: Background A new generation of highly navigable large-bore aspiration catheters and retriever devices for intracranial mechanical thrombectomy has markedly improved recanalization rates, time and clinical outcomes. We report collected clinical data utilizing a new technique based on combined large lumen aspiration catheter and partially resheathed stent retriever (ARTS: Aspiration (catheter)–(stent) Retriever Technique for Stroke). This technique is applied, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(118 citation statements)
references
References 29 publications
4
104
0
1
Order By: Relevance
“…technique, and so forth) and generating backward flow to prevent clot embolization. 3,6,11 The force at the catheter tip depends on only the catheter diameter and the applied pressure and is therefore not altered by resistors. 12 The flow, however, is highly influenced by additional resistors; thus, any additional tubing and valves should be avoided whenever a backward flow is desired.…”
Section: Aspiration Pumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…technique, and so forth) and generating backward flow to prevent clot embolization. 3,6,11 The force at the catheter tip depends on only the catheter diameter and the applied pressure and is therefore not altered by resistors. 12 The flow, however, is highly influenced by additional resistors; thus, any additional tubing and valves should be avoided whenever a backward flow is desired.…”
Section: Aspiration Pumpsmentioning
confidence: 99%
“…1 In past years, the focus of neurointerventional stroke research has shifted from establishing the method to finding the optimal treatment technique. [2][3][4][5][6] Effective blood flow management during the procedure is key to safety and effectiveness. 7 Chueh et al 2 have shown that there are thousands of small clot fragments during thrombectomy that may occlude small arterioles and capillaries.…”
mentioning
confidence: 99%
“…There are also single-arm series on the use of an IAC alone without an SR which suggest that this technique may be as efficacious or even more efficacious than using an SR 3 4 9–11. There are also single-arm series on the SR/IAC combination approach 12. Still others have compared use of balloon guide catheters versus non-balloon guide catheters with SRs 13.…”
Section: Introductionmentioning
confidence: 99%
“…Further experiments will help to validate and confirm the recalcitrance of our bifurcation model. This includes the evaluation of different established modalities for thrombectomy, such as the ADAPT (A Direct Aspiration First Pass Technique) 17 and ARTS (Aspiration-Retriever Technique for Stroke) 12 methods, or primary suction thrombectomy (Fig. 4).…”
Section: Future Experimentsmentioning
confidence: 99%